KARAKTERISTIK HABITAT TARSIUS (Tarsius Sp.) BERDASARKAN SARANG TIDUR DI HUTAN LAMBUSANGO PULAU BUTON PROVINSI SULAWESI TENGGARA - Mansyur, Fadhilah Iqra; Mustari, Abdul Haris; Prasetyo, Lilik Budi (Media Konservasi, 2016)
Tarsier is a nocturnal insectivore primates endemic to Sulawesi including Buton Island. Buton tarsier is only occurrence on the island and its likely status as a distinct species make it more threatened than the other species on the mainland. Moreover, the habitat of this species has been suffering from forest clearance through illegal logging and mining. The aims of this study are to identify the sleeping site of the tarsier and the habitat characteristics surround its sleeping sites. The research were carried out from June to August 2014 at Lambsango Forest, Buton Island, Southeast Sulawesi. The data collected consisting locations and types of sleeping sites, habitat component including abiotic and biotic in each site where the tarsier sleeping site found. The study showed that mostly tarsier lived in the in strangler fig trees (Ficus sp.), rock crevices and sometimes in trees with hollow crevices or trees with vine tangles. Moreover, the study also showed that the sleeping sites mostly found near to the street, seetlement, and forest edge. Vegetation composition and insect’s abundance also influenced the existence of the sleeping location.  Keywords: Buton Island, habitat, Lambusango Forest, nest, tarsier